AKTIVITAS ANTIBAKTERI SABUN CAIR MINYAK ATSIRI DAUN Eucalyptus pellita - Anwar, Mustadi; Hamzah, Farida Hanum; Ayu, Dewi Fortuna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Eucalyptus pellita leaf essential oil has antibacterial activity so it can be used as an additive to liquid soap. This study aimed to determine the inhibitory power of Staphylococcus aureus and Escherichia coli in liquid soap of E. pellita leaf essential oil. This research used a Complete Randomized Design with five treatments and three replications. The treatments were addition of essential oils in consecutive P1(1,15 ml), P2 (1,19 ml), P3 (1,22 ml), P4 (1,30 ml), and P5 (1,35 ml). The data obtained were statistically analyzed using Analysis of Variance (ANOVA) and Duncan’s New Multiple Range Test at 5%. The results showed that addition of E. pellita essential oils significantly affected the density, viscosity, free alkali, degree of acidity (pH), antibacterial test, and flavor of the liquid soap. The best treatment of liquid soap in this research was P5 (addition Eucalyptus pellita essential oil 1,35 ml) which had density 1.07 g/ml g/ml, viscosity 195.87 Cp, free alkali 0.20%, pH 9.80. Antibacterial activity against S. aureus of 15.65 mm and E. coli of 12.91mm.The result of descriptive test of liquid soap showed that the soap has the aroma of E. pellita and the hedonic test for aroma was favored by the panelists.Keywords: Eucalyptus pellita, essential oil, liquid soap, antibacterial.